POTASSIC FERTILIZATION FOR CRAMBE CROP - Rosolem, Ciro Antonio [UNESP]; Steiner, Fabio [UNESP] (Univ Federal Uberlandia, 2014)
There are few studies for the crambe crop (Crambe abyssinica Hochst), and studies that characterize the sufficiency level of K in the soil and leaves are indispensable to support future programs potassium fertilization for this crop of fall/winter. An experiment was carried out to investigate the response of crambe to K soil. The experiment was carried out on a clayey Red Latossol under no-till in Botucatu, S (a) over tildeo Paulo State, Brazil. Treatments consisted of seven K levels in the soil, resulting from the application year (2000 to 2010), the summer crop (soybean), 0, 30, 60, 90, 120, 150 and 180 kg ha(-1) K2O. Before starting the experiment, soil samples were collected at depths of 0-20 cm and soil K contents determined by the resin and Mehlich-1 method. The sufficiency levels of K in soil and leaves were obtained considering the relative yield of 90%. When the levels of soil K extracted by resin and Mehlich-1, are above 88 and 94 mg dm(-3), respectively, equivalent to 26 g kg(-1) K in the leaves, the increase in crop yield of crambe is unlikely. These values should match the sufficiency level of crop and are sufficient to achieve relative grain yield of 90%.
Keywords: Crambe abyssinica Hochst; Potassium availability; Foliar diagnosis; Critical levels